ADEA‐ADEE Shaping the Future of Dental Education III: Assessment in competency‐based dental education: Ways forward. Issue 1 (24th January 2020) - Tonni, Ingrid; Gadbury‐Amyot, Cynthia C.; Govaerts, Marjan; ten Cate, Olle; Davis, Joan; Garcia, Lily T.; Valachovic, Richard W.
Abstract: Assessment in competency‐based dental education continues to be a recognized area for growth and development within dental programs around the world. At the joint American Dental Education Association (ADEA) and the Association for Dental Education in Europe (ADEE) 2019 conference, Shaping the Future of Dental Education III, the workshop on assessment was designed to continue the discussion started in 2017 at the ADEA‐ADEE Shaping the Future of Dental Education II. 1 The focus of the 2019 conference involved examining the potential of entrustable professional activities (EPAs) and current thinking about workplace‐based assessment (WBA) within competency‐based education in the 21st century. Approximately 30 years ago, George Miller wrote about the assessment of competence in medical education and challenged faculty to reach for higher levels of assessment than knowledge or skill. 2 Acknowledging that no one assessment method can result in a valid assessment of competence, Miller proposed a four‐level framework for assessment. The lowest level involves measuring what students know ("knows"), followed by assessment of the skill with which knowledge is applied in relevant tasks or problems ("knows how"). Next is an assessment of task performance in standardized settings ("shows how"), and finally, the highest level assesses the student's performance in the unstandardized clinical workplace ("does"). The 2019 assessment workshop focused on advances in the assessment of learners in the unstandardized workplace—the highest level of Miller's assessment pyramid ("does"). Research has shown that dental education has struggled to implement assessment strategies that meet this level. 3 The workshop brought together individuals from around the world, with an interest in assessment in dental education, to consider how assessment in the "does" level, specifically EPAs and WBA, factors into competence assessment in dentistry/dental education.